Treatment of lattice relaxations in dilute alloys within the Korringa-Kohn-Rostoker Green's-function method - N. Stefanou; P.J. Braspenning; R. Zeller; P.H. Dederichs (Physical Review B, 1987)
We develop a formalism to take into account the lattice relaxation around an impurity within the Korringa-Kohn-Rostoker Green's-function method. Using this formalism and the density-functional theory in the local spin-density approximation we perform first-principles, self-consistent calculations for the electronic structure of some dilute metallic alloys. In particular, we investigate the influence of lattice relaxations on the local magnetic moments in CuMn, CuFe, CuCo, and NiMn.